Establishment and maintenance of persistent infection by Sindbis virus in BHK cells. - Weiss, B (1980)
We have established a persistent infection of BHK cells with a preparation of Sindbis virus heavily enriched in defective interfering (DI) particles. The small fraction of cells that survived the initial infection grew out to form a stable population of cells [BHK(Sin-1) cells], most of which synthesized viral RNA and viral antigens. The presence of DI particles in this virus stock was required to establish this persistent state. BHK(Sin-1) cells released a small-plaque, temperature-sensitive virus (Sin-1 virus) as well as DI particles containing DI RNAs larger than those present in the original stock used to establish the persistent state. A cloned stock of Sin-1 virus, free of detectable DI particles, was able to initiate a persistent infection more quickly and with greater cell survival than the original stock of Sindbis virus containing DI particles. About 2 weeks after the Sin-1 virus-infected cells were cultured, DI RNAs arose and soon became the dominant viral RNA species produced by these cells.